2002
DOI: 10.1074/jbc.m205997200
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Activation of Protein Kinase C-ε by Caspase-mediated Processing and Transduction of Antiapoptotic Signals

Abstract: Several novel protein kinase C (PKC) isozymes have been identified as substrates for caspase-3. We have previously shown that novel PKC⑀ is cleaved during apoptosis in MCF-7 cells that lack any functional caspase-3. In the present study, we show that in vitro-translated PKC⑀ is processed by human recombinant caspase-3, -7, and -9. Tumor necrosis factor-␣ (TNF) triggered processing of PKC⑀ to a 43-kDa carboxyl-terminal fragment, and cell-permeable caspase inhibitors prevented TNF-induced processing of PKC⑀ in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
96
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(101 citation statements)
references
References 28 publications
(25 reference statements)
5
96
0
Order By: Relevance
“…We have previously shown that PKCe protects cells against TNF-induced cell death in MCF-7 cells. 30 We determined whether PKCe overexpression would exert a protective effect against TRAIL-induced apoptosis. MCF-7 cells overexpressing PKCe (MCF-7/PKCe) or vectortransfected control cells (MCF-7/Neo) were treated with different concentrations of TRAIL, and cell viability was determined by the 3-4,5-dimethylthiazol-2-yl-2,5-diphenyltetrazolium bromide (MTT) assay.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that PKCe protects cells against TNF-induced cell death in MCF-7 cells. 30 We determined whether PKCe overexpression would exert a protective effect against TRAIL-induced apoptosis. MCF-7 cells overexpressing PKCe (MCF-7/PKCe) or vectortransfected control cells (MCF-7/Neo) were treated with different concentrations of TRAIL, and cell viability was determined by the 3-4,5-dimethylthiazol-2-yl-2,5-diphenyltetrazolium bromide (MTT) assay.…”
Section: Resultsmentioning
confidence: 99%
“…MCF-7/Neo, MCF-7/PKCe and MCF-7/DN-PKCe cells were generated as described previously. 30 MCF-7/PKCe cells were co-transfected with either 2 mg of empty vector or Bid-pcDNA3.1 together with 2 mg SV40-b-gal plasmids using Fugene HD reagent (Roche Biomedicals) according to the manufacturer's instructions. Transfection efficiency was determined by b-galactosidase expression.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PKC-ε acts a protective role against oxidative stress-induced injury in diverse cell types [49], for example, inhibiting mitochondrial permeability transition pore opening, which prevents apoptosis [50]. Over cleavage prevented its antiapoptotic signal [51]. A down-regulation of PKC- ε by chronic exposure to a phorbol ester was associated with resistance to drug-induced apoptosis in human prostatic carcinoma cells [52].…”
Section: Muscella Et Al -Role Of Egfr In Cisplatin-treated Cells -16mentioning
confidence: 99%